Learning interventions for consultants : building the talent that drives business - London, Manuel; Diamante, Thomas (Fundamentals of consulting psychology book series., 2018)
"Employee development is a driver of economic growth. Employees and organizations are part of what the Danish economist B.A. Lundvall called the learning economy, in which knowledge is the critical resource and the most important process is learning. Today's organizations expect employees to be continuous learners, to maintain and increase their skills and competencies to keep up with the rapid pace of change and competition. This book guides learning consultants in how to design, implement, and support employee development programs. They may work with human resource managers to develop performance management systems that include selection, training, performance appraisal, feedback, and career development. The book is intended for consulting psychologists and those new to consultative roles. It also intends to appeal to nonpsychologists, such as learning consultants, corporate-based facilitators of learning, and others who are interested in specific aspects of training and development. The book comprises of six chapters. Chapter one describes the perspectives that consultants bring to learning interventions. Chapter two focuses on the science of learning, examining seminal theory and research that show the value of learning interventions to individuals, teams, and organizations. Chapter three describes five steps for creating training design and implementation: needs analysis, contracting, design, implementation, and evaluation. Chapter four focuses on the practice of learning, describing learning interventions for adaptive, generative, and transformative learning. Chapter five covers integrating technology into learning interventions. Finally, Chapter six offers recommendations for learning professionals, the challenges they face, and directions for the future."--Preface. (PsycINFO Database Record (c) 2018 APA, all rights reserved)